2014
DOI: 10.7554/elife.02257
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric exchange of multi-protein building blocks between stationary focal adhesions and the cytosol

Abstract: How can the integrin adhesome get self-assembled locally, rapidly, and correctly as diverse cell-matrix adhesion sites? Here, we investigate this question by exploring the cytosolic state of integrin-adhesome components and their dynamic exchange between adhesion sites and cytosol. Using fluorescence cross-correlation spectroscopy (FCCS) and fluorescence recovery after photobleaching (FRAP) we found that the integrin adhesome is extensively pre-assembled already in the cytosol as multi-protein building blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 42 publications
6
57
0
Order By: Relevance
“…(legend on next page) on integrin endocytosis for their proper turnover at MASs has been reported , while recent findings have shown that focal adhesion-interacting proteins display similar kinetics (Hoffmann et al, 2014). Thus, the talin-GFP exchange rate is increased in Parvin mutants; however, the mys b58 GOF allele is sufficient to restore it.…”
Section: Discussionmentioning
confidence: 88%
“…(legend on next page) on integrin endocytosis for their proper turnover at MASs has been reported , while recent findings have shown that focal adhesion-interacting proteins display similar kinetics (Hoffmann et al, 2014). Thus, the talin-GFP exchange rate is increased in Parvin mutants; however, the mys b58 GOF allele is sufficient to restore it.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, individual proteins exchange between the adhesion and cytoplasm within seconds, highlighting the dynamic nature of the adhesion (26,69,70). Again, the exchange rates correlate with myosin forces, and many critical components exchange more slowly and less extensively in the presence of blebbistatin (e.g., paxillin), whereas others exchange more readily (e.g., vinculin) (26).…”
Section: Stabilization and Maturation Of Adhesions By Forcementioning
confidence: 88%
“…By contrast, candidate-based microscopy studies have focused on the architecture, interactions, and dynamics of adhesion complex assembly and disassembly [34,36,37]. For example, recent studies have identified that many adhesome components are pre-assembled as multi-protein building blocks in the cytosol, allowing rapid adhesion complex maturation and turnover [34]. Together these studies have contributed to our understanding of integrin signalling, force generation, and actin regulation and their impact on numerous downstream cellular processes.…”
mentioning
confidence: 95%
“…Proteomic analyses also suggest the existence of a large number of non-canonical adhesome components. By contrast, candidate-based microscopy studies have focused on the architecture, interactions, and dynamics of adhesion complex assembly and disassembly [34,36,37]. For example, recent studies have identified that many adhesome components are pre-assembled as multi-protein building blocks in the cytosol, allowing rapid adhesion complex maturation and turnover [34].…”
mentioning
confidence: 95%